HUBUNGAN PREDIABETES TERHADAP NEUROPATI DIABETIKUM DI KLINIK AISYIYAH MUHAMMADIYAH MEDAN - REKA KHAIRIAWAN REZKI; LITA SEPTINA (LP2MTBM MAKARIOZ, 2021)
Prediabetes is a condition when the blood glucose level exceeds normal, but does not meet the criteria of Diabetes Mellitus(DM). Prediabetes has been world’s health problem, since the prevalence is quite high. Prediabetes can develop into DM inseveral years. Raise in blood glucose level is also related to diabetic neuropathy. To determine the relationship betweenprediabetes and diabetic neuropathy in Aisyiyah Health Clinic in Medan. This study used the correlative analytic method withcross sectional design. The samples are patient from Aisyiyah Muhammadiyah Health Clinic that meets the inclusion andexclusion criteria, using the consecutive sampling method. The data was further analyzed using fisher chi-square test. Theresult of the bivariate analysis of prediabetes and diabetic neuropathy shows the number of p = 1,00 (p>0,05). There is nosignificant relationship between prediabetes and diabetic neuropathy in Aisyiyah Muhammadiyah Health Clinic in Medan.